Current Trends in the Development of Anesthesiology - V. V. Moroz; V. V. Likhvantsev; O. A. Grebenchikov (Общая реаниматология)
The topic of anesthesia is constantly touched upon in the treatises of the V. A. Negovsky Research Institute of General Reanimatology, Russian Academy of Medical Sciences. The Institute's researchers have studied and perfected general and regional anesthesia, intraoperative protection modes during ambulatory surgical interventions. In 2010, a perioperative critical care laboratory was set up for further investigations of the issues and problems of anesthesiology. The laboratory's main scientific areas are to investigate the negative effects of mechanical ventilation during general anesthesia and ways of their overcome; to study the mechanisms of hypoxic preconditioning, and to attempt to put the discovered phenomenon into clinical practice. Progress and prospects in the selected areas are discussed